An experimental study of air flow and heat transfer over in-line flat tube bank - Tahseen, Tahseen Ahmad; M., Ishak; M. M., Rahman (Universiti Malaysia Pahang, 2014)
An experimental study has been made to investigate heat transfer and air flow around flat tube of in-line flat tube banks with laminar forced convection. Measurements were conducted for sixteen tubes in the flow direction;four tubes in the rows, the three air velocity (0.6, 0.8 and 1.0 ms-1) and Reynolds number are ReDh = 527, 703 and 880,where Dh isthe hydraulic diameter of the tube. The total heat flux supplies in all tubes are 967.92, 2258.48 and 3629.70 Wm-2, respectively. The study results indicate that the average Nusselt number of all flat tubes has increased 23.7%-36.7% with Reynolds numbers varying from 527 to 880 at the fixed heat flux; also averageNusselt number has increased11.78% - 23.75% at the heat flux are varying 967.92, 2258.48 and 3629.70 Wm-2, respectively at the Reynolds number Re = 703. In addition, the pressure drop decreaseswith the increase of Reynolds number. The Nusselt number-Reynolds number correlation was found to be 2 1 C Nu  C Re , the correlation yielded good predictions of the measured data with the mean error R2 = 0.992.